Angucyclines containing β-ᴅ-glucuronic acid from Streptomyces sp. KCB15JA151. (15th September 2021) - Kim, Gil Soo; Jang, Jun-Pil; Oh, Tae Hoon; Kwon, Mincheol; Lee, Byeongsan; Lee, Jung-Sook; Ko, Sung-Kyun; Hong, Young-Soo; Ahn, Jong Seog; Jang, Jae-Hyuk
Graphical abstract: Abstract: Two angucyclines, pseudonocardones D (1 ) and E (2 ), were isolated from Streptomyces sp. KCB15JA151. The planar structure was elucidated by comprehensive spectroscopic analysis. The absolute configuration of the sugar unit was determined based on the basis of coupling constants, ROESY, chemical derivatization and HPLC analysis. The biological activities of compounds 1 and 2 were examined by performing a computational target prediction, which led to tests of the antiestrogenic activity. The result suggested that compound 1 might be an ER α antagonist.